Stabilizaton of clayey soil using polyethylene and polypropylene - Fatin Nabilah, Mender (2015)
A number of studies have been conducted recently to investigate the influence of randomly oriented fibers on the geotechnical behavior of grained soils. However, very few studies have been carried out on fiber-reinforced clayey soils. Therefore, this experimental work has been performed to investigate the influence of randomly oriented fiber and systematically oriented inclusion on the geotechnical behavior of clayey soils. This research evaluates the use of waste fiber materials such as polyethylene and polypropylene fiber for the modification of clayey soils. This investigation focuses on the shear strength of the reinforced soils with randomly and systematically included waste fiber materials. The unreinforced soil were subjected to specific gravity test, hydrometer test, Atterberg limits and proctor compaction and unconfined compression test to determine the geotechnical properties. The results for the basic properties of clayey soil are as following, optimum moisture content: 32.5%, maximum dry density: 13.43 kN/m3, specific gravity: 2.51, liquid limit: 74.67%, plastic limit: 45.98% and plasticity index: 28.69%. However, for the reinforced soil were subjected to unconfined compression test only in order to differentiate the shear strength with unreinforced soil. These waste fibers improve the strength properties of clayey soils. The UCS value enhanced with increasing percentage of polypropylene fiber and reached at optimum content on 10% reinforcement where it showed the highest improvement of 730 kN/m2 from 650 kN/m2 and depleted when reach 20% reinforcement. For polyethylene fiber, the reinforced soil showed the highest UCS on 20% reinforcement by 733 kN/m2. The polyethylene and polypropylene fibers can be successfully used as reinforcement materials for the modification of clayey soils.